(untitled) - Timberlake, Karen C. (New York, 2006)
Chemistry: An Introduction To General, Organic, And Biological Chemistry, Ninth Edition makes chemistry exciting to readers by showing them why important concepts are relevant to their lives and future careers. The text retains the many features that have made it so successful: a clear and friendly writing style, a modernized design, Career Focus features, macro-to-micro art work, modern applications and pedagogical tools. Measurements, Atoms and Elements, Nuclear Radiation, Compounds and Their Bonds, Chemical Reactions and Quantities, Energy and Matter, Gases, Solutions, Acids and Bases, Introduction to Organic Chemistry, Unsaturated Hydrocarbons, Organic Compounds with Oxygen and Sulfur, Carboxylic Acids, Esters, Amines, and Amides, Carbohydrates, Lipids, Amino Acids, Proteins, and Enzymes, Nucleic Acids and Protein Synthesis, Metabolic Pathways and Energy Production. For all readers interested in receiving an introduction to general, organic, and biological chemistry.
Keywords: Chemisty; Textbook